2003
DOI: 10.2208/journalam.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bridging Degradation Based Fatigue Analysis of ECC under Flexure

Abstract: This paper proposes a fatigue analysis method of Engineered Cementitious Composite (ECC) under fatigue flexure by applying the concept of fiber bridging degradation. The mechanical degradation of materials under fatigue load is considered a major factor for fatigue crack propagation and subsequent fracture. FEM with the concept of both smeared crack and discrete crack is introduced for representing the consequences of multiple cracks and a localized crack , respectively. The bridging stress degradation law und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…According to the constitutive relation of UHTCC under tension, as shown in Fig. (a), after initial cracking, pseudo strain hardening turned up, and the deformation of UHTCC also developed linearly with a rather small increase in tensile strain. In this stage, no crack emerged in the concrete layer, and the deformation of this layer also behaved linearly on the basis of its tensile constitutive relationship, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the constitutive relation of UHTCC under tension, as shown in Fig. (a), after initial cracking, pseudo strain hardening turned up, and the deformation of UHTCC also developed linearly with a rather small increase in tensile strain. In this stage, no crack emerged in the concrete layer, and the deformation of this layer also behaved linearly on the basis of its tensile constitutive relationship, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate fatigue evaluation of the 15 material mixes shown above without completing millions of cycles of experimental fatigue loading, a fatigue model for ECC materials developed by Suthiwarapirak & Matsumoto (2004) is used. This model, based on previous work by Zhang (1998) and Suthiwarapirak & Matsumoto (2003), is shown as Equation 1.…”
Section: Estimation Of Service Lifementioning
confidence: 99%
“…Fatigue failure characteristics and fiber bridging characteristics of UHTCC under flexure were investigated and it was found that UHTCC exhibited significantly higher fatigue life and more ductility than concrete, polymer cement mortar and steel fiber reinforced concrete [21][22][23][24][25]. In addition, flexural fatigue behavior of concrete beams with UHTCC layer [26][27][28] and the tensile failure property of UHTCC under monotonic and cyclic tensile loads [29,30] has been studied.…”
Section: Introductionmentioning
confidence: 99%